Analytical Approach to Polarization Mode Dispersion in Linearly Spun Fiber with Birefringence - Vinod K. Mishra (International Journal of Optics)
The behavior of Polarization Mode Dispersion (PMD) in spun optical fiber is a topic of great interest in optical networking. Earlier work in this area has focused more on approximate or numerical solutions. In this paper we present analytical results for PMD in spun fibers with triangular spin profile function. It is found that in some parameter ranges the analytical results differ from the approximations.